Singapore's building stock a multi-scale documentation and analysis of transformations - Hassler, Uta 1950- (Hirmer Verlag GmbH, 2020)
State-of-the-art Singapore is constantly transforming and rejuvenating her building stock. The book documents and analyses these transformations of the efficiently organized global city over the past two centuries at multiple spatial scales. This book offers an alternative history of Singapore's urban development: the history of construction, demolition and reconstruction. The collection of essays assesses what the changes in Singapore's building stock meant for the preservation of physical and cultural values for the long view. In three sections - the island scale, the district scale, and the building scale - different data sources come together to show the relationship between development policies, the morphology of Singapore's built environments and the speed of its transformation. Photos, maps and numerical charts illustrate the lost and new, revealing accidental survivors as well as carefully staged relics from the past
Keywords: Geschichte; Städtebau; Stadtentwicklung; Singapur